Speech Production and Malocclusion: A Review - Nelvi Yohana; Handoko Handoko (JURNAL ARBITRER, 2023)
The article focuses on speech production in relation to malocclusion. It investigates how malocclusion could affect sound production and articulating clearly. The article also discusses how orthodontists could fix malocclusion and improve the sound production. Speech production is a complicated process involving several speech organs, including the mouth cavity. Malocclusion can have an adverse effect on pronunciation, especially on specific speech sounds. It can also cause compensatory articulation problems, which can affect pronunciation further. Certain speech sounds, such as /s/, /z/, /t/, /d/, /l/, /r/, / θ /, and /t/, can be affected by malocclusion. Different types and levels of malocclusions may have different effects on pronunciation. It is necessary to speak with an orthodontist to determine the most appropriate therapy for malocclusion. Proper diagnosis and treatment can assist in reducing the impact on pronunciation. Additionally, speech and language therapy may help in the development of speech. The article concludes with an overview of the available treatments for speech production, the potential impacts of malocclusion can be minimized.